1980
DOI: 10.1002/qua.560170214
|View full text |Cite
|
Sign up to set email alerts
|

Electronic absorption and emission spectra of nucleic acids and their components: Some questions of theory and experiment

Abstract: The results of calculations of the transition energies and polarization in nucleotide bases performed by the CNDO/S CI method are compared with experimental data for long-wavelength and vacuumabsorption bands. The calculations and the analysis of experimental data testify to the existence of n -T* transitions in the first absorption bands of the bases. The study of double-stranded polynucleotides and DNA hypochromism based on the theoretical electronic characteristics of the bases and perturbation theory is pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 51 publications
1
12
0
1
Order By: Relevance
“…The lowest electronic state of guanine is unambiguously characterized to be a * state, and the lowest n * state appears to be much higher in energy by about 0.5 eV to 0.9 eV. 13,14,16 Therefore, it is expected that the vibronic mixing between the n * and * states occurs in a much higher frequency region, perhaps well outside the range of the spectrum experimentally observed ͑Fig. 1 of Ref.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The lowest electronic state of guanine is unambiguously characterized to be a * state, and the lowest n * state appears to be much higher in energy by about 0.5 eV to 0.9 eV. 13,14,16 Therefore, it is expected that the vibronic mixing between the n * and * states occurs in a much higher frequency region, perhaps well outside the range of the spectrum experimentally observed ͑Fig. 1 of Ref.…”
Section: Resultsmentioning
confidence: 89%
“…of the -* transition. 9,10 As for the relative locations of these states, Lipiński 13 and Hug and Tinoco 14 suggested that the n * state is located between the two lowest * states, whereas Stewart and Davidson, 10 Danilov et al, 16 and Takahata 17 proposed that the n * state is the lowest singlet excited state of adenine. Broo also concluded that the geometrically relaxed lowest excited state of adenine has an n * character, while a related compound, 2-aminopurine, has a strong * character that gives the molecule totally different photophysical properties.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations